2016
DOI: 10.1007/s11126-016-9483-6
|View full text |Cite
|
Sign up to set email alerts
|

Death Anxiety Resilience; a Mixed Methods Investigation

Abstract: Objectives:Research was conducted examining how death anxiety influenced PTSD and mental health among people who have experienced a lifethreatening event.Design & Methods:This study was conducted using undergraduate university students in Lithuania. The study used a mixed-method design and in phase 1, participants (N=97) completed self-report questionnaires that gathered information on demographics, death anxiety, trauma and well-being. Results:Data indicated a significant correlation between death anxiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Resilience is important for self-protection. Hoelterhoff and Chung found that coping mechanisms allowed participants to develop resilience against the effects of death anxiety and minimize its negative impact on mental health [ 47 ]. Interventions to promote resilience should be available for cancer patients [ 24 ] to help them deal with their impending death.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is important for self-protection. Hoelterhoff and Chung found that coping mechanisms allowed participants to develop resilience against the effects of death anxiety and minimize its negative impact on mental health [ 47 ]. Interventions to promote resilience should be available for cancer patients [ 24 ] to help them deal with their impending death.…”
Section: Discussionmentioning
confidence: 99%
“…Wong, 2009). Furthermore, as both fear of death and alexithymia are negatively related to psychological health and are related positively with depression (i.e., Burke, McArthur, Daryanani, Abramson, & Alloy, 2018;Hoelterhoff & Chung, 2017;Lumley & Jasinski, 2014;Ziadni, Jasinski, Labouvie-Vief, & Lumley, 2017), their decrease can be considered to be an intensification of psychological well-being (P. T. P. Wong et al, 1994). In addition, knowing how to recognize and better understand emotions and consequently communicating them, even if they are negative, improves psychological well-being (Cacciatore, Thieleman, Killian, & Tavasolli, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This result confirms that DE, when managed in an appropriate manner, can help adolescents to reflect on mortality and transcendence, reducing anxiety and improving the ability to deal with the topic, which is already emphasized in the literature (Doka, 2015; Knight & Elfenbein, 1993; McClatchey & King, 2015; Testoni, Ronconi, et al., 2018; W. Wong, 2009). Furthermore, as both fear of death and alexithymia are negatively related to psychological health and are related positively with depression (i.e., Burke, McArthur, Daryanani, Abramson, & Alloy, 2018; Hoelterhoff & Chung, 2017; Lumley & Jasinski, 2014; Ziadni, Jasinski, Labouvie-Vief, & Lumley, 2017), their decrease can be considered to be an intensification of psychological well-being (P. T. P. Wong et al., 1994). In addition, knowing how to recognize and better understand emotions and consequently communicating them, even if they are negative, improves psychological well-being (Cacciatore, Thieleman, Killian, & Tavasolli, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy can be a functionally more powerful buffer (e.g., Bandura, 1982;Bandura, 1988). The concept of anxiety buffer is more complex and may include several components that empirically prove to contribute to the alleviation, blocking or buffering such existential anxieties (e.g., Hoelterhoff & Chung, 2017). Self-esteem alone is one component of a cluster of anxiety buffer.…”
Section: C) the Dynamics Of Existential Anxieties Activationmentioning
confidence: 99%